Cone, Tetrahedron and Unit Interval - Azram, Mohammad (2011)

(untitled)
In this article we will establish a bijection from a unit solid circular cone onto unit interval with some notions. Consequently, the unit interval will be embedded into unit solid circular cone . Further, imposing a Hausdorff metric on unit interval, we will be able to convert the same bijection into a homeomorphism from unit solid circular cone onto unit interval. We will also establish a homeomorphism from unit solid circular cone onto a tetrahedron.